Treinamento com vibração do corpo todo resulta em ganho de força muscular e mobilidade funcional em indivíduos com doença de Parkinson - Sá, Barbara Eden de Oliveira [UNESP] (2015)
Patients with Parkinson's disease (PD) have varying degrees of muscle weakness, mobility impairment, postural instability and other motor abnormalities. Recently training with vibration has been used in PD patients with promising results, but not yet conclusive. The aim of this study was to analyze the effect of a protocol using the vibration of the whole body (VCT) in muscle strength and functional mobility in individuals with PD (n = 10). Before the training protocol subjects performed an initial evaluation consisting of: evaluation of isometric muscle strength of the flexor and extensor of the knee and functional mobility (Short Physical Performance Battery-SPPB). The same procedures as the initial assessment were performed at the end of training. The volunteers performed five weeks of training on the vibration platform: training was conducted with the subjects standing in two positions: a) feet apart in a stable and comfortable position with knees extended; b) feet apart and knees bended. In each position the vibration was performed in five series of 1 minute long, with 1 minute interval between each set, and 5 minutes between the first and second positions. There were two weekly sessions lasting 30 minutes each. After the five weeks the volunteers were reassessed. The pre and post-intervention data were compared using the ANOVA test for repeated measures and post hoc Bonferroni (p <0.05). This study showed that five weeks of therapy with VCT, 2 sessions per week resulted in significant improvement in isometric muscle strength of knee flexors and extensors (F = 11.558, p = 0.009) and functional mobility (F = 11.558, p = 0.009) in individuals with PD